1997
DOI: 10.1063/1.474544
|View full text |Cite
|
Sign up to set email alerts
|

Point-ion versus density functional calculations of electric field gradients in ordered GaInP2

Abstract: Articles you may be interested in Calculation of electric-field gradients based on higher-order generalized Douglas-Kroll transformations

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…For both the double- and triple-ζ basis sets, polarization functions were added to bromine's basis set while the other atoms' basis sets remained unchanged. Mixed basis sets were chosen because the majority of the EFG is local , and some basis sets are not available for Br. Sadlej's pVTZ 47,48 basis set, which is available for Br, was not used due to convergence difficulties for these molecules.…”
Section: Methodsmentioning
confidence: 99%
“…For both the double- and triple-ζ basis sets, polarization functions were added to bromine's basis set while the other atoms' basis sets remained unchanged. Mixed basis sets were chosen because the majority of the EFG is local , and some basis sets are not available for Br. Sadlej's pVTZ 47,48 basis set, which is available for Br, was not used due to convergence difficulties for these molecules.…”
Section: Methodsmentioning
confidence: 99%
“…It has been shown that a point charge model is not able to properly predict the EFG distributions in these type of systems. 49 A good model should rely on first-principles input data. We address the problem in two ways: first, we make ordered and randomized structural models using supercells, with the compositions x = 0.5 and x = 0.3125 and calculate their EFGs with DFT.…”
Section: Dft Modelingmentioning
confidence: 99%
“…It has received a great deal of attention because it affects the electro-optical properties of the alloy and reveals interesting surface-controlled epitaxial growth processes. [1][2][3][4][5][6][7][8][9][10][11][12][13] Although many techniques, such as excitation photoluminescence ͑PLE͒, are well suited to measuring the effects of ordering on electro-optical properties, they can only estimate the degree of ordering in a sample by relying on theoretical calculations modeling the effects of ordering on the electronic band structure. 4,5 Recently, nuclear magnetic resonance spin echo measurements have been applied to the evaluation of the order parameter.…”
mentioning
confidence: 99%
“…This technique of determining the order parameter, however, is also based on theoretical estimates, in this case of the EFG using the point-ion model or the local-density-functional formalism method. 6,7 A technique is therefore needed that directly determines the order parameter without relying on the results of electronic structure calculations.…”
mentioning
confidence: 99%
See 1 more Smart Citation